Overview of Students' Interest and Motivation in Participating in PJOK Learning Activities in Class VII of Hubbul Aitam Middle School, Lubuklinggau City - Ardi Affandi; Drajat Friansah; Erick Salman (Nusantara Education Press, 2023)
This research aims to determine the overview of students' interest and interest in participating in PJOK learning activities in class VII of Hubbul Aitam Middle School, Lubuklinggau City. The research method used in this research is descriptive quantitative. The sampling technique in this research uses purposive sampling, which looks at the characteristics of the sample with certain reasons in mind, so the sample in this research is male, 20 students in grades VII and VIII. The research was conducted at Hubbul Aitam Middle School, Lubuklinggau City. Data collection was carried out using questionnaires and interviews. From the research results it was concluded that 1) Student interest in participating in PJOK learning activities in class VII of Hubbul Aitam Middle School, Lubuklinggau City for the student interest category was very high at 5.00% (1 student), the student interest category was high at 90.00% (18 students ) and the moderate student interest category was 5.00% (1 student). 2) Student motivation in participating in PJOK learning activities in class VII of Hubbul Aitam Middle School, Lubuklinggau City, the high student motivation category was 65.00% (13 students), the medium student motivation category was 25.00% (5 students) and the low student motivation category of 10.00% (2 students).